2000
DOI: 10.1029/1999wr900328
|View full text |Cite
|
Sign up to set email alerts
|

Funneled flow mechanisms in a sloping layered soil: Laboratory investigation

Abstract: Abstract. Artificial capillary barriers are being used to divert water away from sensitive underground regions. Conversely, funneled flow over natural capillary barriers may increase the danger of groundwater contamination by decreasing the travel time and contact area. There have been relatively few experimental studies of capillary barrier flow patterns. In this study, water was applied uniformly across the top surface of a backlit tilting chamber, 1 cm thick, 110 cm high, and 180 cm long, in which a coarse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 33 publications
1
68
0
Order By: Relevance
“…In particular, tank experiments performed in the laboratory under controlled conditions [e.g., Wildenschild and Jensen, 1999;Walter et al, 2000] are very valuable. Ursino et al [2001aUrsino et al [ , 2001b observed in a tracer experiment in a quasi two dimensional tank, an artificial, heterogeneous soil profile made out of sandy structures (thin layers), swooping from a mildly heterogeneous state under wet conditions, to a state characterized by highly preferential paths under drier conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, tank experiments performed in the laboratory under controlled conditions [e.g., Wildenschild and Jensen, 1999;Walter et al, 2000] are very valuable. Ursino et al [2001aUrsino et al [ , 2001b observed in a tracer experiment in a quasi two dimensional tank, an artificial, heterogeneous soil profile made out of sandy structures (thin layers), swooping from a mildly heterogeneous state under wet conditions, to a state characterized by highly preferential paths under drier conditions.…”
Section: Introductionmentioning
confidence: 99%
“…After a certain distance, the matric potential of the fine material becomes sufficiently less negative and the water starts to percolate into the coarser material (Ross, 1990;Walter et al, 2000). The ERT results show that the plume spreads further into deeper layers in the downslope direction (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…There are several types of preferential flow which may be caused e.g. by textural interfaces, soil water repellency, air entrapment, soil aggregation and spatial heterogeneity (Walter et al, 2000;Ritsema & Dekker, 2000;Wang et al, 1998;Lennartz et al, 1999).…”
Section: Introductionmentioning
confidence: 99%